Peran Work Engagement dalam Memoderasi Pangaruh Employee Retention Terhadap Kinerja Pegawai pada Bank Muamalat KC Pekalongan Raya - Giat Waluyo; Chalimah (Universitas Muhammadiyah Surabaya, 2025)
This study aims to analyze the effect of Employee retention onEmployee performance, with work engagement serving as a moderating variable at Bank Muamalat KC Pekalongan Raya. The research is grounded in the importance of Employeeretention and work engagement in supporting optimal performance, particularly amid the uneven achievement ofKey Performance Indicators (KPI) across branches. The sample consisted of all 46 Employees of Bank Muamalat KC Pekalongan Raya, selected using a saturated sampling technique. Data were collected through a Likert-scalequestionnaire distributed via Google Forms and processedusing SmartPLS version 4.0. The data analysis techniqueemployed Partial Least Squares (PLS) through the evaluationof the outer model, inner model, and hypothesis testing. The results indicate that both Employee retention and workengagement have a positive and significant effect on Employeeperformance. However, work engagement does not significantly moderate the relationship between Employeeretention and Employee performance.